2010
DOI: 10.1007/s00425-010-1322-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling and redox status alteration of recalcitrant tea (Camellia sinensis) seed in response to desiccation

Abstract: Tea seed is believed to be recalcitrant based on its sensitivity to chilling or drying stress. Reactive oxygen species (ROS) and alterations in cytosolic redox status have been implicated in intolerance to desiccation by recalcitrant seed, but there is little information available regarding how ROS are regulated in seeds susceptible to drying stress. We investigated changes in protein expression and activity in tea embryo in response to desiccation using physiological and proteomic methods. Results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 45 publications
(51 reference statements)
3
41
0
Order By: Relevance
“…The homogenates were centrifuged at 12,000g for 15 min at 4°C, and the total soluble protein concentration of supernatants was determined by the Bradford method (Bradford 1976). The activities of MDHAR, DHAR, APX, and GR were determined as described (Chen et al 2011).…”
Section: Antioxidant Enzyme Activity Assaysmentioning
confidence: 99%
“…The homogenates were centrifuged at 12,000g for 15 min at 4°C, and the total soluble protein concentration of supernatants was determined by the Bradford method (Bradford 1976). The activities of MDHAR, DHAR, APX, and GR were determined as described (Chen et al 2011).…”
Section: Antioxidant Enzyme Activity Assaysmentioning
confidence: 99%
“…This may have been due to loss of the selective permeability of cellular membranes, suggesting that membrane integrity is vital, since any desiccation damage may have immediate consequences for the seeds' germinability. Recent studies have confirmed that decreased viability of recalcitrant seeds was closely related to the accumulation of membrane lipid peroxides, such as in Camellia sinensis [47]; Quercus robur [48]; Trichilia connaroides [49]; and other recalcitrant seeds. Thus, the desiccation of G. biloba seeds accompanied by a deepening degree of membrane lipid oxidation led to the severe damage of the membrane system, causing a large accumulation of MDA.…”
Section: Changes Of Mda Content In G Biloba Seeds During Desiccationmentioning
confidence: 99%
“…Dehydration and rehydration during seed development or during germination are associated with high levels of oxidative stress (Dandoy et al, 1987;Rajjou et al, 2012). Overaccumulation of reactive oxygen species (ROS) can cause oxidative damage to a wide range of cellular components and cause DNA damage, reducing the seed's ability to germinate (Bailly et al, 2008;Chen et al, 2011;Parkhey et al, 2012). An optimal range of ROS levels is required for successful germination (Bailly et al, 2008).…”
mentioning
confidence: 99%